Unmasking silence and impunity: the Zimbabwe Peace Project’s e-activism in a polarised political dispensation - Mashingaidze, Terence M (Routledge, 2021)
This study is an exploration of the use of technology-mediated interventions by the Zimbabwe Peace Project (ZPP) in checkmating the country’s insidious culture of political violence and impunity. It disentangles the ZPP’s strategies and the composite reactions they triggered from state functionaries and the aligned security apparatus. The ZPP exploited and deployed an Internet-circulated monthly newsletter, bulk short message service (SMS) alerts, smartphones, radio and Facebook to shine a spotlight on injustice. It is argued that the ZPP’s whistle-blowing strategies used against human rights violators were not necessarily intended to secure immediate perpetrator conviction; rather, they were a partial but exigent attempt at using perpetrator exposure to reveal extralegal activities and checkmate the country’s culture of impunity. The ZPP’s cybernetic naming and shaming strategies embarrassed some offenders, as evidenced by the intelligence operatives and the police’s constant harassment and arrests of ZPP-affiliated activists. The state-controlled media compounded this pressure by casting aspersions on the ZPP’s bona fides, labelling it a foreign-funded organisation that was attempting to destabilise the country. Finally, this study is informed by a broad evidentiary base that includes ZPP reports on its e-archive, oral interviews, policy documents and newspaper accounts.